Bacterial Biofilm Inhibition: A Focused Review on Recent Therapeutic Strategies for Combating the Biofilm Mediated Infections - Srinivasan, Ramanathan; Santhakumari, Sivasubramanian; Poonguzhali, Pandurangan; Geetha, Mani; Dyavaiah, Madhu; Xiangmin, Lin (Frontiers in Microbiology, 2021)
Biofilm formation is a major concern in various sectors and cause severe problems to public health, medicine, and industry. Bacterial biofilm formation is a major persistent threat, as it increases morbidity and mortality, thereby imposing heavy economic pressure on the healthcare sector. Bacterial biofilms also strengthen biofouling, affecting shipping functions, and the offshore industries in their natural environment. Besides, they accomplish harsh roles in the corrosion of pipelines in industries. At biofilm state, bacterial pathogens are significantly resistant to external attack like antibiotics, chemicals, disinfectants, etc. Within a cell, they are insensitive to drugs and host immune responses. The development of intact biofilms is very critical for the spreading and persistence of bacterial infections in the host. Further, bacteria form biofilms on every probable substratum, and their infections have been found in plants, livestock, and humans. The advent of novel strategies for treating and preventing biofilm formation has gained a great deal of attention. To prevent the development of resistant mutants, a feasible technique that may target adhesive properties without affecting the bacterial vitality is needed. This stimulated research is a rapidly growing field for applicable control measures to prevent biofilm formation. Therefore, this review discusses the current understanding of antibiotic resistance mechanisms in bacterial biofilm and intensely emphasized the novel therapeutic strategies for combating biofilm mediated infections. The forthcoming experimental studies will focus on these recent therapeutic strategies that may lead to the development of effective biofilm inhibitors than conventional treatments.